1989
DOI: 10.1042/bj2590925
|View full text |Cite
|
Sign up to set email alerts
|

Aurintricarboxylic acid is a potent inhibitor of phosphofructokinase

Abstract: Aurintricarboxylic acid (ATA) was found to be a very potent inhibitor of purified rabbit liver phosphofructokinase (PFK), giving 50% inhibition at 0.2 microM. The inhibition was in a manner consistent with interaction at the citrate-inhibitory site of the enzyme. The data suggest that inhibition of PFK by ATA was not due to denaturation of the enzyme or the irreversible binding of inhibitor, since the inhibition could be reversed by addition of allosteric activators of PFK, i.e. fructose 2,6-bisphosphate or AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…This value is higher than the IC 50 reported by McCune et al [33]. The rabbit muscle isozyme was used in the work presented in this paper, while McCune et al used the rabbit liver isozyme [33]. Moreover, the value reported by McCune et al [33] was measured at pH 7.3, while the current study was conducted at pH 8.0.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…This value is higher than the IC 50 reported by McCune et al [33]. The rabbit muscle isozyme was used in the work presented in this paper, while McCune et al used the rabbit liver isozyme [33]. Moreover, the value reported by McCune et al [33] was measured at pH 7.3, while the current study was conducted at pH 8.0.…”
Section: Resultsmentioning
confidence: 61%
“…After fitting the data by non-linear regression to Equation 1, the IC 50 was determined to be 3.9 2 ± 0.35 μM. This value is higher than the IC 50 reported by McCune et al [33]. The rabbit muscle isozyme was used in the work presented in this paper, while McCune et al used the rabbit liver isozyme [33].…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10] ATA is also known to inhibit enzymes that do not bind to nucleic acids, such as Phe:tRNA ligase, aminopropyltransferase, phosphofructokinase and several enzymes required by NAD(H)/NADP(H). [11][12][13][14] More recently, a study conducted by our group as well as a study conducted by Liang et al reported that ATA inhibits protein tyrosine phosphatases (PTPs). 15,16 ATA has also been shown to prevent apoptotic cell death in a variety of cell types including breast cancer MDA-231 and MCF-7 cells, macrophage RAW 264.7 cells and rat pheochromocytoma PC12 cells.…”
Section: Introductionmentioning
confidence: 99%